2013
DOI: 10.1038/bjc.2013.118
|View full text |Cite
|
Sign up to set email alerts
|

KRAS-mutation status in relation to colorectal cancer survival: the joint impact of correlated tumour markers

Abstract: Background:Mutations in the Kirsten Ras (KRAS) oncogene are common in colorectal cancer (CRC). The role of KRAS-mutation status as a prognostic factor, however, is unclear. We evaluated the relationship between KRAS-mutation status and CRC survival, considering heterogeneity in this association by tumour and patient characteristics.Methods:The population-based study included individuals diagnosed with CRC between 1998–2007 in Western Washington State. Tumour specimens were tested for KRAS exon 2 mutations, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
151
7
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(185 citation statements)
references
References 38 publications
22
151
7
5
Order By: Relevance
“…30). However, there was no difference, in our cohort, in OS between WT and KRAS-mutant patients (P ¼ 0.675; HR, 1.11; 95% CI, 0.67-1.85), although some authors have reported that the presence of KRAS mutation is indicative of poor outcome (31). Nevertheless, literature analysis tends to show that there is sometimes confusion around the terms prognostic and prediction of therapeutic response.…”
Section: Discussioncontrasting
confidence: 64%
“…30). However, there was no difference, in our cohort, in OS between WT and KRAS-mutant patients (P ¼ 0.675; HR, 1.11; 95% CI, 0.67-1.85), although some authors have reported that the presence of KRAS mutation is indicative of poor outcome (31). Nevertheless, literature analysis tends to show that there is sometimes confusion around the terms prognostic and prediction of therapeutic response.…”
Section: Discussioncontrasting
confidence: 64%
“…KRAS gene plays a central role in tumor development by regulating the expression of proteins that are involved in cell proliferation and survival, metastasis and angiogenesis. [4][5][6] In colorectal carcinoma, KRAS mutations are present in 30-40% of patients. 7 Activating mutations in KRAS are responsible to anti-EGFR therapy resistance (Cetuximab or Panitumumab) in metastatic colorectal cancer (mCRC).…”
Section: Introductionmentioning
confidence: 99%
“…KRAS mutations in colon cancer contribute to aggressive cancer phenotype and poorer prognostic [21].…”
Section: Resultsmentioning
confidence: 99%